Early stage venture funding in South Africa - Naidoo, Dilin (My University, 2014)
Entrepreneurship is a key ingredient to reducing unemployment and increasing economic growth. In South Africa, historical data points to an issue with entrepreneurs getting access to early stage venture capital. Venture capitalists usually back numerous ventures with the hope that some of them will produce significant returns while the rest will fail. The data-collection method was qualitative by nature and centred on eight interviews with either portfolio or investment managers at VC funds or divisions operating in South Africa. The data provided by the respondents was analysed and compared to the propositions identified in the literature review and finally conclusions and recommendations were made. While they both disburse funds to new ventures, public and private sector VCs share differing interests and motivations. While private sector VC are driven purely by economics, public sector VC have to additionally help government achieve policy objectives which means that decisions made are sometimes not purely based on rands and cents. In addition, while government is making an effort to grow the VC industry and entrepreneurship in general, most respondents feel that they are not focusing on the right areas. In reality, the list of South African entrepreneurs who are commercialising successful products and services overseas is growing. This country has to stem this tide through creating an environment which incentivises and motivates entrepreneurs. Finally, VCs in South Africa must be commended on adapting their business models to cater for the local environment. VCs are critical in helping to create liquidity in a very risky area of the financial industry. In the interests of growing entrepreneurship in the country, private VCs need to do more to reduce the possible tensions between themselves and the public VCs through transferring knowledge and sharing risk through co-financings for example. The enabling environment for entrepreneurship in South Africa is fractured. Immediate measures need to be taken to harmonise the interactions between iii VCs, entrepreneurs and government in order to improve entrepreneurship. If levels of entrepreneurship increase, the benefits will trickle down to VCs and government as well.
MBA thesis
Keywords: Venture funding; Angel funding; Entrepreneurship